Psychometric Test of Shoulder Pain and Disability Index (SPADI) Indonesian Version in Frozen Shoulder Et Causa Capsulitis Adhesive - Fitriani, Dessy; Komalasari, Dwi Rosella (Jurnal Ilmiah Kesehatan (JIKA), 2024)
Frozen shoulder is a common condition tha causes pain and resulting limitation of movement affecting 2-5% of the general population. It is more common in women than men, generally aged 40-70 years, so a valid and consistent instrument is needed to see pain and disability in shoulder pathology with the Shoulder Pain and Disability Index (SPADI) instrument. The purpose of the study was to determine the validity and reliability of the Shoulder Pain and Disability Index (SPADI) questionnaire in the Indonesian version. This research was a quantitative study with a methodological approach. The research was conducted in September 2023 in two places, namely Kustati Hospital and UNS Hospital, with a total sample of 41 subjects using the purposive sampling technique. The SPADI instrument was given twice with a distance of 2 weeks, getting very good test-retest reliability results (ICC 0,986; p-value <0,001; and 95% CI 0,975–0,993). Internal consistency is good, with a Cronbach's alpha value of 0,935. The results of the content validity test was based on the corrected item total correlation value above 0,3. The conclusion of this study is that the Indonesian version of the SPADI instrument is declared reliable and valid for use in patients with frozen shoulder e.c adhesive capsulitis to asses the level of pain ad disability in shoulder.